Virtual identities from virtual environments - Prince, Melvin (Handbook of Research on Digital Media and Advertising: User Generated Content Consumption, 2011)
The creation of identities in immersive online digital environments has become commonplace in consumer behavior. Consumers frequently enter into socially networked, computer mediated environments (CME’s) as avatars. A user can design his or her avatar by choosing typologies of facial features, body types and clothing styles. The chapter concerns Avatar analysis as a system for generating and analyzing consumer information of practical value to marketers. Avatar analysis enhances understanding of brand perceptions and meanings, discovers new ways of positioning and differentiating brands, and provides insights for improving the effectiveness of brand communications. Using websites such as Second Life to draw avatars, consumer identity projections are elicited based on consumers’ perceptions and interpretations of their own digital figure drawings i.e., virtual social identities of consumers and brands. These identity projections disclose their real and ideal selves, brand-as-a-person, and imagery of a typical brand user.
Citation Key Alias: lens.org/013-773-118-538-567
Keywords: dept.mkt

Domestic Product Involvement and Consumer Willingness to Buy Domestic Products: Empirical Testing of a Cognitive Consistency Theory Framework - Prince, Melvin (Journal of International Consumer Marketing, 2020)
This study investigates biases affecting domestic products willingness to buy (WTB). An interdisciplinary perspective uses the cognitive consistency theory as the framework for the development of a new model. The model includes domestic product involvement (DPI). The impact on WTB is predicted by consumer ethnocentrism, and product judgment, driven by DPI are tested with survey data from an adult sample of 255 UK consumers. The study concludes with observations about the value of research findings for marketing practice. © 2020 Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] WOS:000517943000001
Keywords: Cognitive consistency theory; consumer ethnocentrism; dept.mkt; domestic product involvement; peer-reviewed; product judgment; willingness to buy

Consumer Cosmopolitanism in the Age of Globalization - Prince, Melvin (Business Expert Press, 2012)
Cosmopolitans are individuals with a distinctive kind of extended national and international orientation, a global vision, and sense of belonging to the world. These people are sophisticated and importantly engaged in the cultures outside of local geographical boundaries. But what do we know about them as consumers—their origins, values, media usage, and buyer behavior? This unique book details much about this group, and fills a knowledge gap that has long been overlooked largely because other related marketing areas have overshadowed and overlooked the notion of cosmopolitan consumers. Until this book, in fact, there has been no single authoritative source that directly and comprehensively covers the field of consumer cosmopolitanism. This book also includes original essays by an all-star cast of contributors, giving you an introduction to a powerful new approach to marketing, eclectically packed with novel ideas and insights that noticeably advance the marketing field and bring it more fully into the age of globalization.
Keywords: Business & Economics / Consumer Behavior; Consumer behavior; dept.mkt; faculty_collection

Using intuitive awakening for business students to enhance strategic thinking skills - Prince, Melvin; Priporas, Constantinos (Australasian Marketing Journal (AMJ), 2018)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-466-664-601-02X, pop00274, princeUsingIntuitiveAwakening2018a tex.type: [object Object]
Keywords: dept.mkt; peer-reviewed

Consumer morality and moral consumption behavior: literature domains, current contributions, and future research questions - Yaprak, Attila; Prince, Melvin (Journal of Consumer Marketing, 2019)
Purpose: The literature on consumer morality and consumption is spread widely across many research streams and would benefit from grouping under selected themes so that scholars’ work can be guided by the compass of these themes. It is also important to add studies to each of these themes to serve as gateways that will guide new research. The aim of this special issue of the Journal of Consumer Marketing was to achieve precisely this purpose. The purpose of this paper is to open the gate to the exploration of the themes that today describe this landscape. Design/methodology/approach: The paper assesses the contributions made in each of several domains to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. There are at least four domains of morality and moral consumption studies as follows: the formation of the moral self and moral identity; moral identity and ethical consumption; moral reasoning (cognitive processes) and moral choice; and the moral self and marketing. Each of these domains of work provides insight into the moral consumption phenomenon. Findings: The authors highlight the development of the moral self and underscore the significance of the relationship between identity development and the individual’s moral actions and by extension the significance of that relationship in moral consumption. Also, the paper adds to the current discussion on morality and ethical consumption by underscoring their interlinked nature and how that linkage can drive consumption behavior, highlight the cognitive processes involved in moral choices and how consumers reason to arrive at those choices. Finally, the authors provide examples of the workings of moral identity and reasoning in consumption contexts more directly. Originality/value: Each of these morality and moral consumption domains of work provides unique insights into the moral consumption phenomenon; thus, it is important to disseminate the contributions made in each domain to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. In this paper, the authors offer contemporary original samples of key contributions to each of these domains. © 2019, Emerald Publishing Limited.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-197-857-855-353, pop00162, yaprakConsumerMoralityMoral2019a tex.type: [object Object]
Keywords: Consumer morality; Ethical consumption; Moral choice; Moral consumption; Moral identity; Moral reasoning; dept.mkt; peer-reviewed

Switching costs and ad agency-client relationship longevity: an exploratory study - Davies, Mark; Prince, Melvin (Services Marketing Quarterly, 2011)
A model of switching costs is applied to ad agency-client relationships using agency theory. Switching costs are comprised of set-up costs that create barriers to switching to new agencies and exit costs that are barriers to severing relationships with current agencies. Switching cost theory offers insights into why large clients can maintain agency relationships. A survey of American clients shows how client size is associated with set-up and exit costs. These relationships are explained through diversity and scope of services, the creative risk associated with major brands, and the need for more sophisticated monitoring, each acting as switching barriers, extending longevity. © Taylor & Francis Group, LLC.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-432-635-158-979 tex.type: [object Object]
Keywords: Account longevity; Client size; Switching costs; dept.mkt

Advertising agency compensation, client evaluation and switching costs: an extension of agency theory - Davies, Mark; Prince, Melvin (Journal of Current Issues and Research in Advertising, 2010)
We develop a theory of advertising agency compensation, client evaluation and switching costs, with extensions to agency theory. When clients are exposed to high switching costs, they become more vulnerable to the risk of agency costs. In response, clients can select compensation and evaluation decisions that convey fairness, signal their commitment, and invite agency reciprocity. With high switching costs, outcome-based compensation and formal evaluation procedures are likely. High switching costs are associated with signifi'cant relationship investments, mature relationships, large clients, formal evaluation, and with clients that use their agencies as strategic partners. Clients surveyed in North America support the theory. © 2010 Taylor and Francis Group, LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-534-427-868-948 tex.type: [object Object]
Keywords: dept.mkt

Does the Netherlands-based consumer disidentification model work in the US? - Prince, Melvin; Kwak, Lynn (EMPGENS | Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI) concept and its impact on product purchase behavior. In his investigation, a predictive model that included CDI as an exogeneous factor in domestic product preference was tested on adult second-generation immigrants who were born in, and lived in, the Netherlands. The model also incorporated consumer ethnocentrism (CET) as a second predictor variable. Josiassen's study showed that CDI negatively affected the purchase of products made domestically or by domestic firms. Conversely, CET was found to have a positive effect on the purchase of these products. Furthermore, relationships of CDI and CET to purchase intentions were independent of each other. In the Netherlands model, both variables were hypothesized to explain domestic product preference directly and indirectly through domestic product judgment. This paper replicates and assesses the generalizability of the CDI construct and model. Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit, but a slightly below acceptable structural fit. © 2020, University of South Australia. All rights reserved.
tex.ids: princeDoesNetherlandsbasedConsumer2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85091584869 type: Article
Keywords: Consumer disidentification; Cross-cultural; Domestic product preference; Ethnocentrism; Second-generation immigrants; dept.mkt; peer-reviewed; ⛔ No DOI found

A latent class analysis of brand prestige - Prince, Melvin; Davies, Mark (Model Assisted Statistics and Applications, 2009)
Core constructs are necessary as a basis for scale development in brand prestige research. This study examines the theoretical rationale for two such concepts - brand excellence and status conferral - and uses latent class scaling in an empirical test as to whether they are both important independent dimensions of prestige brands. Based on the analysis, these concepts are shown to be consistently present for two brands in two diverse product categories. The research calls into question earlier work on the measurement of brand prestige that was premised on a one-dimensional concept of prestige. Further studies are needed to explore the dimensionality and substantive structure of the brand prestige concept, to confirm or disconfirm findings from this research. © 2009 IOS Press. All rights reserved.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/038-210-773-767-532 tex.type: [object Object]
Keywords: Brand excellence; Latent class scaling; Prestige brand; Status conferral; dept.mkt

Dynamics of trust between clients and their advertising agencies: advances in performance theory - Davies, Mark; Prince, Melvin (Academy of Marketing Science Review, 2005)
Citation Key Alias: lens.org/197-806-583-049-540
Keywords: dept.mkt; ⛔ No DOI found

The animal within - Prince, Melvin; Davies, Mark (Business Strategy Review, 2004)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-656-633-545-989 tex.type: [object Object]
Keywords: dept.mkt

Inside Advertiser and Agency Relationships: A Hands-On Guide for Practitioners - Prince, Melvin; Davies, Mark (Lulu. com, 2006)
Keywords: dept.mkt

Secondary Risk in COVID-19 Vaccination Intentions: A Theoretical Contribution to the Protection Motivation Paradigm - Prince, Melvin; Kim, Young (Journal of Applied Social Science, 2023)
This study presents an original model that features the emotion of fear of COVID-19 as a direct effect on vaccination intentions. A central research question addressed in the study is what roles do the emotion of fear of contracting COVID-19 and the threat posed by uptake of the COVID-19 vaccination play in levels of vaccination intention? The study used a structural equation model (SEM) and applied the SmartPLS 3.2.6 data analysis tool for model estimation and multivariate analysis variables. A key finding is that vaccination resistance is strongest when fear of COVID-19 is lower, and vaccination threat higher. Vaccination threat appraisal and vaccination intention were found to have a negative relationship. Response costs at higher levels lessen motivation for COVID-19 vaccination. Research implications include research-based targeting of differing segments by their primary fear, either fear of COVID-19 or of the preventative vaccine.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mkt; peer-reviewed

A model of academic dishonesty intentions: mediating effects of machiavellianism and differential association - Prince, Melvin; Wang, Emma (Journal of Further and Higher Education, 2024)
Past studies of academic dishonesty typically have been grounded in the theory of planned behaviour. Key predictors of academic dishonesty variables under this framework generally have been attitudes towards academic dishonesty, the impact of peer pressure to engage in such acts, and individual perceptions of related acts. However, planned behaviour theory is silent about the significant impact on academic dishonesty of past academic dishonesty behaviours. The objective of the present study is to analyse, through the lens of social learning theory, the effects of past behaviours that predispose academic dishonesty: differential association, i.e., the effects of individual learning, through interaction with others, of the values, attitudes, techniques, and motives for deviant behaviour, on the prediction of academic dishonesty intentions. Additionally, the study tests the effects of Machiavellianism, or dishonest and deceptive behaviours on the relationship between past academic dishonesty acts and academic dishonesty attitudes. Results of the study reveal that differential association with cheating acceptors strengthens the relationship between academic dishonesty attitudes and intentions. Additionally, Machiavellianism at higher levels intensifies the relationships between past academic dishonesty behaviours and contemporary academic dishonesty attitudes.
_eprint: https://doi.org/10.1080/0309877X.2024.2375307
Keywords: Past cheating behaviour; academic dishonesty; cheating; dept.mrk; differential association; machiavellianism; peer-reviewed; social learning

Impact of risk aversion, reactance proneness and risk appraisal on travel destination risk perception: - Prince, Melvin; Kim, Young Kyu (Journal of Vacation Marketing, 2021)
The aim of the study is to investigate the motivational effects of tourist traits and risk appraisal on tourist destination risk perception. Risk appraisal involves subjective estimates of vulnerability to a threat and the threat’s consequential severity. Fear levels influence both of these elements of risk appraisal. Individual differences in reactance proneness and risk aversion are introduced into the study model to more fully account for differences in travel destination risk perceptions. The study design involves US adults, who have used their passports for international travel in the past 5 years. Travel risk assessments were studied for four destination sites: London, Tokyo, Kuala Lumpur and Istanbul. A general structural model is developed to test hypotheses about antecedents and consequents of risk appraisal and destination risk perception. © The Author(s) 2021.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85100166276
Keywords: dept.mkt; peer-reviewed

Industry Applications of Market Sensing Foreword to the Special Issue of Journal of Marketing and Management - Prince, Melvin; Priporas, Constantinos-Vasilios (Journal of Marketing and Management, 2014)
Num Pages: 5 Place: Beverly Hills, United States
Keywords: Business And Economics–Management; Business And Economics–Marketing And Purchasing; Competition; Competitive advantage; Consumers; Knowledge management; Marketing; Product development; Product lines; Research; SWOT analysis; dept.mkt; ⛔ No DOI found

Continuties in Market Sensing - Prince, Melvin; Priporas, Constantinos-Vasilios (Market Sensing Today, 2015)
The concept and framework of market sensing was introduced by George Day more than 20 years ago into the strategic marketing literature and especially the philosophy of the market-driven organization. Market sensing can be considered an expression of a company's capabilities to scan the external environment. It does this by using real time data and intelligence to understand business or uncertain changes, to meet the current and future needs of the market, increase customer value, and outperform competitors. Market sensing enables managers to resist complacency, as well as to exploit opportunities and to design appropriate competitive strategies in order to remain successful in today's uncertain, rapidly changing, and hypercompetitive market. The present volume, Market Sensing Today, is essential reading in the marketing discipline, given the rapidly escalating innovative developments in market sensing techniques. This book of essays by acknowledged experts in the field fills an important knowledge gap and provides a realistic basis for strategy. It is replete with real-life examples of market sensing that illustrate actionable ideas for immediate impact that will improve organizational learning and accelerate growth. This book of contemporary tested and comprehensive concepts and methods grounded in diverse and rich experience is intended to stimulate creativity and insightful approaches for educators offering courses in strategy as well as for practitioners involved in crucial strategic decision making.
Keywords: Business & Economics / Marketing / General; Marketing research; dept.mkt; faculty_collection

Market Sensing Today - Prince, Melvin; Priporas, Constantinos-Vasilios (Business Expert Press, 2015)
Today's practicing marketers and scholars are confronted with a wide array of conflicting and imprecise information about best practices by which to search, gather, consolidate and interpret market information. Consequently, the need has never been greater to optimize market sensing to generate managerial actions that efficiently and effectively utilize knowledge of emerging consumer needs and competitive threats. This book addresses these urgent concerns. In essence, Market Sensing Today will cover, in ground-breaking ways, the following marketing managerial areas: * marketing opportunities associated with conventional and progressive bases of segmentation. * trends in market segment size and growth affecting long-range planning. * strategic direction for reaching future goals. * managerial understanding of assumptions competitors make about themselves. * the direction of current market strategies. * adding to the knowledge of a firm's core competencies. * how new market knowledge is best integrated into a firm's market intelligence system. * best ways to ensure the quality of information underlying decisions. * how benchmarking improves with market sensing. * best approaches for translating business issues into projects. * ways that key information may be disseminated within firms. * how proposed strategic changes are promoted by market sensing. * roles customer satisfaction insights play in policy. This book will address these key issues and more, to advance theory, research and practice based on latest developments in this vital field. It will show how to re-formulate traditional models that no longer work.
Keywords: dept.mrk; faculty_collection

Qualitative analysis and the construction of causal models - Prince, Melvin; Manolis, Chris; Tratner, Susan (Qualitative Market Research: An International Journal, 2009)
Purpose: The purpose of this paper is to provide a methodology by which qualitative analyses serve as rich source materials for discovery of theoretically cogent interrelations between latent variables. Design/methodology/approach: In an illustrative case, qualitative data are collected from US franchisee managers from a single branded franchise of automotive repair outlets. Qualitative analysis of franchisee experiences and attitudes is critical for construction of a causal model used to predict conflict intensity between franchisee managers and franchisors. Findings: The model is based on franchisees' normative expectations for resource allocation within the franchise; and their perceptions of franchisor normative violations, which are determinative of grievances, distrust, and hostility. This theoretical orientation serves to generate a system of interrelated empirically testable propositions. Research limitations/implications: In principle, the primary limitation of using qualitative analysis for the construction of causal models is the fruitfulness of the theoretical orientation shared by the qualitative analyst and the causal modeler. Practical implications: The methodological approach advanced in this paper advances qualitative research and causal modeling beyond the individual contributions. Qualitative analysis infuses variables and process imagery into causal modeling. In turn, causal modeling elaborates the qualitative analysis and makes explicit logical connections between variables. Originality/value: This paper advances a methodology by which qualitative analysis and causal model construction may be usefully integrated. Theory-based qualitative analysis may be formalized to map latent concepts and their interrelations. Further, operational measures of these concepts may be adduced from the analysis of textual data. © Emerald Group Publishing Limited.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-869-015-006-521 tex.type: [object Object]
Keywords: Modelling; Qualitative methods; dept.mkt

Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism; Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

The moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions - Prince, Melvin; Yaprak, Attila N.; Palihawadana, Dayananda (Journal of Consumer Marketing, 2019)
Purpose: This paper aims to develop a model that explains the moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions. The authors build their work on moral foundations theory and the social theories of Emile Durkheim. Design/methodology/approach: Theory-building from general theories of motivation is grounded in cultural norms, and empirical research is conducted to test theoretical propositions. Findings: The focus is on the theoretical implications of binding or individualism morals of consumers within social groups. Consequently, variables in the model relate to ethical themes of community, autonomy and divinity. This theory posits that, for a variety of considerations, loyalty has a direct and positive effect on consumer ethnocentrism and on consumer cosmopolitanism. Serendipitously, other moral foundations have negative effects. The authors theorize that negative relationships exist between authority and consumer cosmopolitanism, and between sanctity and consumer ethnocentrism. This model also illustrates that consumer ethnocentrism positively predisposes favorable domestic product judgments. Research limitations/implications: New ethical factors in consumer dispositions affecting product purchase decisions are explored. Hypotheses can be empirically replicated and moderated in future research. Practical implications: Marketers can use the variables of personal values, moral foundations and gender role identity to fashion marketing communications and to target selective consumer segments. Social implications: The persuasion process of social marketing will be enhanced by understanding relevant motives. Originality/value: The use of the fine-grained moral foundation antecedents to predict consumer predispositions of ethnocentrism and cosmopolitanism is without precedent. © 2019, Emerald Publishing Limited.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-190-319-130-88X, pop00157, princeMoralBasesConsumer2019a tex.type: [object Object]
Keywords: Consumer ethics; Consumer ethnocentrism; Consumer psychology; dept.mkt; peer-reviewed

The Diogenes Effect in retail buyer information processing - Prince, Melvin; Kwak, Lynn; Priporas, Constantinos Vasilios (Journal of Retailing and Consumer Services, 2019)
The search for an ethical vendor who is honest and trustworthy in the exchange process is conceptualized as the Diogenes Effect, an innovative concept. In the light of this effect, the theoretical framework of the current study's model involved retail buyer responses to vendor persuasive communications. The model was tested by having a sample of retailer buyers complete a survey of information processing in the search for a product and vendor. This study innovatively links vendor communication effects to retailer buyer decision-making and evaluations by incorporating and integrating elements of Elaboration Likelihood Theory. Contributing to theory-building, it was found that when retailer buyers searched for a vendor with an ethical orientation, the result was intensified central processing of information and decreased peripheral information processing. This was especially salient when retailer buyers had greater longevity of professional experience. The next stage, information processing, led to feedback that enabled assessment of vendor trustworthiness. Finally, the research measured the level of fulfillment in the post-purchase phase. In the end, typical outcomes included the generation of favorable expectations of vendor performance, as well as the positive impact of those heightened favorable expectations on greater satisfaction with the value ultimately received from the vendor.
7 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000468124200016 tex.eissn: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Diogenes; Diogenes effect; Elaboration likelihood model; Expectations; Information processing; Retailer buying decision; Satisfaction; decision making; dept.mkt; information processing; modeling; peer-reviewed; retailing

The effects of part-time MBA programs on students: the relationships between students and their employers - Prince, Melvin; Burns, David J; Manolis, Chris (The Journal of Education for Business, 2014)
The authors explore how the relationship between part-time master of business administration (MBA) students and their employers changes as students proceed through their MBA program by examining the degree to which students are integrated into their employer organizations. Significant positive relationships observed between students’ progress through their MBA program and the integration factors of coworker support and future prospects with their employers suggest that an MBA education can have a positive effect on employee–employer integration levels. Consequently, in addition to increasing business knowledge and skills, an MBA degree appears to assist with integrating employees and employers. © 2014, Copyright © Taylor & Francis Group, LLC.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/087-299-392-333-109 tex.type: [object Object]
Keywords: MBA education; coworker support; dept.mkt; graduate education; part-time MBA students; training

Leading Edge Marketing Research: 21st-Century Tools and Practices - Kaden, Robert J.; Linda, Gerald; Prince, Melvin (SAGE Publications, 2012)
This book explores new and leading edge marketing research approaches as successfully practiced by visionaries of academia and the research industry. Ideal as either a supplementary text for students or as a guidebook for practitioners, this book showcases the excitement of a field where discoveries abound and researchers are valued for solving weighty problems and minimizing risks. The authors offer rich new tools to measure and analyze consumer attitudes, combined with existing databases, online bulletin boards, social media, neuroscience, radio frequency identification (RFID) tags, behavioral economics, and more. The reader will profit from the numerous contemporary case studies that demonstrate the key role of marketing research in corporate decision-making.
Keywords: Business & Economics / Marketing / Research; Marketing research; dept.mkt; faculty_collection

A model of job performance, job satisfaction, and life satisfaction among sales and sales support employees at a pharmaceutical company - Prince, Melvin; Engle, Robert L; Laird, Kenneth R (Journal of Pharmaceutical Marketing & Management, 2003)
This study investigates the influence of role conflict, role ambiguity, and role strain on job performance, job satisfaction, and life satisfaction among field sales and company sales support employees in a single pharmaceutical company. Because this study is based on data from a single company, these results may not necessarily be generalized to all companies in the industry. In the present research, a path model of the process reveals important variations in response to role conflict, role ambiguity, and role strain between the two classes of employees. For both classes, the influence of decreased role ambiguity is generally positive for measured outcomes. However, reductions in role conflict, while lessening role strain, are likely to result in lower job performance for field sales employees. Decreases in role strain, while improving life satisfaction, may lead to lower job satisfaction for sales support employees. © 2003, Informa UK Ltd All rights reserved: reproduction in whole or part not permitted. All rights reserved.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-485-139-151-393 tex.type: [object Object]
Keywords: Job performance; dept.mkt; job satisfaction; life satisfaction; pharmaceutical sales; role strain

CEO archetype identity drives organization culture - Prince, Melvin; Forr, James; Wardlaw, Jim; Plummer, Joseph (Journal of Leadership Studies, 2019)
In the current study the relationships between CEO archetypes and organizational climate were examined. Archetypes are historical, mythical, and cultural representations that are shared in our collective unconscious. Data were collected from a CEO and his employees, using a mixed methods research approach which involved the Zaltman Metaphorical Elicitation Technique (ZMET), as well as personality measures and quantitative assessments of organizational climate. The CEO archetype as perceived by employees is that of a benevolent patriarch which mirrors the CEO's self-concept as caring for the well-being of employees. Employees ascribed the stress-free and nurturing organizational climate to the CEO's archetypical leadership style. However, their organizational climate, in principle, leads to excessive employee familistic dependence on the CEO for making important organizational decisions and supplying creative ideation. The present study of a CEO archetype and its bearing on organizational climate is unique, filling an important gap in management knowledge. Implications of the study involve the channeling of its insights about the archetype-embedded organizational climate, so as to better select administrative managers, improve organizational communication trust and openness, stimulate creative innovation, handle organizational crises, and generally promote employee well-being. © 2019 University of Phoenix
3 citations (Crossref) [2023-10-31]
Keywords: dept.mkt; peer-reviewed

Here, there and everywhere: a study of consumer centrism - Prince, Melvin; Davies, Mark; Cleveland, Mark; Palihawadana, Dayananda (International Marketing Review, 2016)
Purpose - A first objective is to add insight into how constructs of ethnocentrism, xenocentrism and cosmopolitanism relate to each other. Knowledge of how these constructs overlap or work together in affecting consumer preferences will offer global marketers insights for designing appropriate marketing strategies. The second objective is to extend this knowledge by examining the correspondence of these three constructs to a nomological network of dispositional concepts pertinent for product positioning and market segmentation. The third objective is to empirically examine the extent to which the measures, construct structure and associative relationships are robust in different national research settings. The paper aims to discuss these issues. Design/methodology/approach - Surveying British and American consumers, this study examines and analyzes the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts: consciousness-of-kind, global consumption orientation, materialism and natural environment concern. Findings - The hypothesized negative links between CET-XEN and CET-COS, and the predicted positive connection between XEN-COS were all confirmed on the latent factor results for the combined data set. The negative correlation between CET-XEN was of a considerably lower magnitude than that for CET-COS. Originality/value - To date, no research has used an identity theory framework and simultaneously examined in a cross-cultural context the interrelationships of consumer ethnocentrism consumer xenocentrism and cosmopolitanism - and their differentiating linkages to a multiplicity of consumer dispositions.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/102-838-974-401-396 tex.type: [object Object]
Keywords: Cross-cultural studies; Ethnocentrism; Global marketing; Green issues; Market segmentation; Marketing; dept.mkt; peer-reviewed

Knowledge and skills transfer between MBA and workplace - Prince, Melvin; Burns, David J; Lu, Xinyi; Winsor, Robert D (Journal of Workplace Learning, 2015)
Purpose-This paper aims to use goal-setting theory to explain the transfer of knowledge and skills between master of business administration (MBA) and the workplace. Design/methodology/approach-Data were obtained by an online survey of MBA students enrolled in at four US graduate business schools. These were a public and private institution in the Northeast region, a private sectarian institution in the Midwest region and a private institution in the Pacific region. All students worked while attending the university. The sampling frame consisted of each school’s MBA enrollees. Questionnaires were distributed to a random cross-section of part-time students at each graduate school of business representative of returned by 144 students. The profiles of responders were consistent with parameters for the entire MBA student population. Findings-The research shows that multiple goals of reciprocal knowledge and skills transfer may be in harmony and mutually reinforcing. In principle, each goal is more likely to be attained with greater economy of effort than might be surmised. Additionally, the same forces may act similarly to facilitate attainment of two well-integrated goals, in this case transfer betweenMBAstudies and work, as well as between work and MBA studies. Research limitations/implications-The present study involved participants from part-time public and private MBA granting institutions in the USA. The study tested and extended goal-setting theory and introduced the innovative concept of reciprocal transfer. Future studies should seek to generalize the findings to a broader population of part-time MBA students, especially from other nations. Despite its strengths, the findings of this study need to be interpreted in the perspective of some limitations. The current study did not measure transfer climates in either the organization or university settings. Transfer climates undoubtedly have an important bearing on transfer outcomes. Practical implications-Review of the present study suggests that a positive MBA environment is needed to influence motivation to learn and perceptions of the MBA program’s utility, thereby promoting transfer of knowledge and skills to MBA studies from the workplace. A supportive work-to-MBA-studies transfer climate will lead to more active learning of course content that has greater relevance for achieving career goals. Potentially generalizable from the organizational transfer climate literature (Rouiller and Goldstein 1990; Rouiller and Goldstein 1993), positive transfer from work to MBA studies will occur when appropriate situational cues and consequences are present in the program. Social implications-A constructive implication suggested by the findings of this study would be the intervention and transfer management by educators to structure and strengthen the university transfer climate of their part-time MBA programs. Traditionally, the concept of transfer climate has been primarily applied to employee workplace training activity and job performance. The university culture of the MBA student might emphasize and reward continuous learning from workplace experiences. Opportunities at the university should be provided for the exercise of newly acquired workplace skills that reinforce MBA learning experiences. Originality/value-This is the first study that shows how learning goals and performance goals are integrated in the context of a new concept, i.e. reciprocal transfer of knowledge and skills betweenMBA and workplace settings. It also demonstrates, for the first time, the impact of learning and motivation for MBAstudies and perceived utility ofMBAprogram on the extent of transfer of learning and skills from the workplace to the university setting. © Emerald Group Publishing Limited.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-480-418-077-781 tex.type: [object Object]
Keywords: Knowledge transfer; Learning orientation; Management education; Performance; dept.mkt

Here, There and Everywhere: The Polycentric Consumer - Cleveland, Mark; Prince, Melvin (Marketing Challenges in a Turbulent Business Environment, 2016)
Identity is recognized as a powerful antecedent of behavior. Social identity denotes the incorporation of culture into a person’s self-concept. A strong correspondence exists between identity with a given social unit and commitment to group values/norms, and thus, how much influence the social unit exerts on the person’s attitudes and behaviors. As a psychological construct, social identity research requires probing how individuals subjectively interpret their own affiliation with one or several collectivities. Cultures are increasingly emancipated from geography in the global era. Because contemporary consumers are continuously exposed to a variety of cultural influences, they may develop polycentric identities. As companies and markets integrate, a key international market segmentation topic relates to consumers’ mindsets about home and extraneous countries/cultures, and subsequently, the products connected with these entities. To date, no research has simultaneously examined the interrelationships of consumer ethnocentrism (bias towards products from one’s national culture), consumer xenocentrism (i.e., preference or orientation towards products from a culture other than one’s own), and cosmopolitanism (i.e., a yearning for and adeptness at mastering cultural diversity) in a single study. Employing an online survey, and drawing from a representative sample (n = 269) of American consumers drawn from all 50 states (plus D.C.), this research also examines the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts (all of which are established in the marketing literature): materialism, consciousness-of-kind, external orientation (cultural open-mindedness and consumption of foreign media), global consumption orientation, and natural environment concern. The survey contained a total of 60 scales corresponding to the 8 constructs, along with a series of key demographic measures. Exploratory and confirmatory factor analyses were applied to the construct measures. Various analytical techniques were employed (tests for convergent/discriminant validity, bivariate correlations, t-tests, MANOVA, two-step clustering, as well as path analyses using structural equation modelling) to test the 19 proposed theoretical hypotheses. Most hypotheses were supported, in terms of statistical significance and magnitude, as well as directional valence. Associative network memory theory and signaling theory implicate how consumers decide from a constellation of local, foreign, and global product options. Upon activation of a brand node by way of retrieval cues (product categories, brand names, and so forth), linkages such product attributes and semantic associations (e.g., ingroups/outgroups and corresponding levels of felt identification) become salient. Firms can manipulate signals, including associations towards or away from countries/cultures, to position products and persuade consumers. Vertical segmentation, the conventional approach to adapting marketing strategies, entails developing marketing mixes for each country, from the near limitless combination of demographic, economic and psychographic variables. Due to the globalization of media and the widespread movement of products and peoples across borders a growing number of researchers instead advocate horizontal segmentation, whereby similar groups of consumers are targeted with an essentially uniform marketing strategy, irrespective of where they might live. Individuals’ inward and outward dispositions—towards their own and different countries, cultures, and products—are sound candidate constructs for designing horizontal strategies.
1 citations (Crossref) [2023-10-31] Citation Key Alias: clevelandHereThereEverywhere2016a, lens.org/002-903-745-679-063
Keywords: Consumer Ethnocentrism; External Orientation; Foreign Medium; Semantic Association; Social Unit; dept.mkt

Consumer centrism : an integrative review: BAM 25th Annual Conference, Building and Sustaining High Performance Organisations in a Challenging Environment - Davies, Mark Alexander; Manolis, C; Prince, Melvin; Windsor, R D (2011)
Keywords: dept.mkt; ⛔ No DOI found

Uniting theory and empirical research: market sensing and marketing research - Prince, Melvin; Gabay, G; Priporas, Constantinos; Moskowitz, H (Quantitative research methods in consumer psychology: contemporary and data driven approaches, 2018)
Quantitative consumer research has long been the backbone of consumer psychology producing insights with peerless validity and reliability. This new book addresses a broad range of approaches to consumer psychology research along with developments in quantitative consumer research. Experts in their respective fields offer a perspective into this rapidly changing discipline of quantitative consumer research. The book focuses on new techniques as well as adaptations of traditional approaches and addresses ethics that relate to contemporary research approaches. The text is appropriate for use with university students at all academic levels. Each chapter provides both a theoretical grounding in its topic area and offers applied examples of the use of the approach in consumer settings. Exercises are provided at the end of each chapter to test student learning. Topics covered are quantitative research techniques, measurement theory and psychological scaling, mapping sentences for planning and managing research, using qualitative research to elucidate quantitative research findings, big data and its visualization, extracting insights from online data, modeling the consumer, social media and digital market analysis, connectionist modeling of consumer choice, market sensing and marketing research, preparing data for analysis;, and ethics. The book may be used on its own as a textbook and may also be used as a supplementary text in quantitative research courses.
Keywords: dept.mkt

An integrative framework of buyer-supplier negative relationship quality and dysfunctional interfirm conflict - Prince, Melvin; Palihawadana, Dayananda; Davies, Mark A. P.; Winsor, Robert D. (Journal of Business-to-business Marketing, 2016)
Purpose: Problems of relationship quality and interfirm conflict in business-to-business settings are serious concerns that need to be addressed. Thus, the authors have engaged in an extensive review to promote an understanding of these complex issues. This article develops an integrated framework for analyzing wide-ranging relations between individual representatives and patterns of interfirm incompatibility for managerial control.Methodology/approach: The review involves numerous sources that include articles and monographs. A theoretical framework is constructed to integrate fragmented empirical data. In particular, social identity and commitment-trust theories are mobilized for this framework.Findings: The review of studies has a substantial consistency with the theoretical framework. The article outlines a causal chain from interpersonal agent dissimilarities to dysfunctional buyer-supplier relations, culminating in interfirm pathological conflict. Moderating factors in the causal chain are: agent identity differentiation (for interpersonal dissimilarity), supplier relations mismanagement (for buyer-supplier relationship quality), and interfirm opportunism (for interfirm pathological conflict). Buyer-supplier interfirm incompatibility mediates the causal link between interpersonal dissimilarity and buyer-supplier relationship quality. Identity differentiation, the validation of one's self-image, is introduced as a process that determines buyer-supplier agent interpersonal dissimilarity judgments. This framework uses a contextual perspective. It describes interactions between observations of micro-level phenomena of interpersonal dissimilarities and macro-level models of interfirm fit. From a managerial perspective, interpersonal relations between individual buyer and supplier agents may be further strengthened by such strategies as expanding the scope of the interpersonal relationship, relaxation of role responsibilities, and volunteering business-related contact referrals.Originality/value: A new theoretical framework has been devised to predict and explain relationship quality and interfirm pathological conflict in the business-to-business context. The framework contributes to the value of the knowledge base by serving as a means for building new diagnostic tools for assessment of interfirm behavioral issues affecting exchanges. New concepts are introduced to enhance current literature on business-to-business marketing. The framework provides concreteindicators that operationally define ideas and enable or improve measurement for empirical modeling.
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-679-568-636-829 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: business marketing; dept.mkt; industrial marketing; relationship quality; similarity; supplier compatibility

A model of trust and compliance in franchise relationships - Davies, Mark A. P.; Lassar, Walfried; Manolis, Chris; Prince, Melvin; Winsor, Robert D. (Journal of Business Venturing, 2011)
Despite the danger of franchisee non-compliance as a severe impediment to overall franchise operation and performance, there is currently minimal understanding of the key factors that lead to these behaviors. Using a foundation of relational exchange theory, we construct and test a model that demonstrates how two distinct forms of trust, based upon perceptions of franchisor integrity and franchisor competence, are critical to explaining the roles that relational conflict and satisfaction play in influencing franchisee compliance. Implications of these findings are then demonstrated to have compelling relevance to the effective management of franchise systems. (C) 2009 Elsevier Inc. All rights reserved.
161 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-297-800-195-412 tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Compliance; Conflict; Franchising; Reciprocity; Satisfaction; Trust; dept.mkt

The psychology of consumer ethnocentrism and cosmopolitanism: a five-country study of values, moral foundations, gender identities and consumer orientations - Prince, Melvin; Yaprak, Attila; Cleveland, Mark; Davies, Mark A. P.; Josiassen, Alexander; Nechtelberger, Andrea; Nechtelberger, Martin; Palihawadana, Dayananda; Renner, Walter; Supekova, Sona Chovanova; Von Wallpach, Sylvia (International Marketing Review, 2020)
Purpose: The purpose of this paper is to examine the extent to which personal values, moral foundations and gender-role identities affect, in sequence, consumers' constructions of their ethnocentric and cosmopolitan orientations. Achieving a better understanding of the psychological makeup of consumer ethnocentrism and cosmopolitanism should help managers better design international market segmentation and brand positioning strategies. Design/methodology/approach: The study's conceptual framework is anchored in attitude and values theories, and focuses on the social categorizations that consumers make and how these contribute to the formation of their ethnocentric and cosmopolitan orientations. Drawing data from consumers living in five European countries, we test our theoretical conjectures through structural equation modeling approaches, including multigroup analysis at the country level, as well as the identification and scrutiny of potential pan-European consumer segments. Findings: Findings show that personal values, moral foundations and gender-role identities do exert direct and indirect (partially mediated) effects on the formation of consumers' ethnocentric and cosmopolitan orientations. These provide numerous insights for managers in terms of how they can segment domestic and international markets, as well as how to position products and communicate brand strategies. Research limitations/implications: The study focused on consumers' personal and role identities and offers implications based on data gathered from a sample of five European countries. Future work should broaden this perspective by including other identity facets, such as religious and ethnic identities, as well as product-category and brand-specific outcomes, in order to help develop a more comprehensive picture of the psychology underpinning consumers' identity-related orientations, and their effects on consumer behavior. Future research should also study these issues in a broader geographical context, by including national markets that have culturally diverse populations as well as places with dissimilar cultural and economic profiles. Originality/value: The study shows that individuals' personal values, moral foundations and gender roles have a strong effect on the formation of consumer ethnocentrism and consumer cosmopolitanism orientations. Consideration of how these antecedent constructs operate in concert to shape consumers' in- versus out-group orientations has been overlooked in the international marketing literature. Beyond the ramifications for theory, the study offers numerous substantive managerial implications in terms of how consumers are likely to respond to local and global/foreign products/brands based on these orientations. © 2020, Emerald Publishing Limited.
18 citations (Crossref) [2023-10-31] WOS:000537142600001
Keywords: Consumer cosmopolitanism; Consumer ethnocentrism; Gender role identity; International market segmentation; Moral foundations; Values; dept.mkt; peer-reviewed